1992
DOI: 10.1139/z92-125
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of dragonfly nymphs across a pH gradient in south-central Ontario lakes

Abstract: ~L L A R D , J. B., and BERRILL, M. 1992. The distribution of dragonfly nymphs across a pH gradient in south-central Ontario lakes. Can. J. Zool. 70: 878-885. Exuviae of 37 species of dragonflies were collected from the emergent vegetation of 19 small ( < 3 5 ha) lakes across a pH gradient (range 4.9-8.1) in south-central Ontario to assess the effect of low environmental pH on species richness and diversity. The number of species present in a lake was not significantly correlated with lake pH. Two measures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…In south-central Ontario, Pollard & Berrill (1992) found decreased anisopteran diversity and increased Leucorrhinia abundance in fishless lakes .…”
Section: Discussionmentioning
confidence: 91%
“…In south-central Ontario, Pollard & Berrill (1992) found decreased anisopteran diversity and increased Leucorrhinia abundance in fishless lakes .…”
Section: Discussionmentioning
confidence: 91%
“…Thus, the persistence of stream salamander populations may be low in chronically acidic stream reaches, as well as in streams that suffer from acute acidic events. By comparison, fish and some invertebrates comprise the most acid sensitive of aquatic taxa, with lethal effects occurring in fish when the pH drops below 6.0 [28] and in dragonflies when pH is less than 5.8 [29]. Yet stream salamanders are not the most tolerant of aquatic organisms; some invertebrates can be extremely tolerant of acidic conditions, such as the caddis fly Ptilostomis postica , which exhibited 100% survival at experimental pH levels of 3.2 [30].…”
Section: Discussionmentioning
confidence: 99%
“…Water quality is thought to affect firefly abundance as the direct determinant of larval habitat quality. Though many studies have found that the sensitivity to acid varies among aquatic insects (Ward 1992), from highly tolerant dragonflies (e.g., Pollard and Berrill 1992) to particularly sensitive mayflies (e.g., Courtney and Clements 1998), the positive influence of relatively high pH (range: 6.07-8.46) on firefly abundance indicated that the Genji-firefly larvae were relatively sensitive to water acidification. The positive relationship between DO (range: 6.26-9.12) and firefly abundance is consistent with the generally accepted knowledge that DO is an environmental variable of considerable importance to many aquatic insects (Ward 1992;Williams and Feltmate 1992).…”
Section: Discussionmentioning
confidence: 99%